2020
DOI: 10.46451/ijclt.2020.06.05
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Face-to-face and Online Teaching of Written and Spoken Chinese to Adult Learners: An Edinburgh-Sheffield Case Study

Abstract: We report a study comparing teaching written and spoken Chinese separately to adult learners without prior knowledge of Chinese in the traditional classroom setting and in the online format. The best way of introducing Chinese characters remains one of the major challenges in teaching Chinese as a foreign language: different methods have been used in practice and more empirical evidence is needed to identify their advantages and limitations. In a crossover design, we compared groups which received either four-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
1
7
0
4
Order By: Relevance
“…Further, concerning the practical aspects of the EFL education environment, students found it "less appealing and engaging due to its limitations" (Ali, 2020;Angdhiri, 2020;Abbasi et al, 2020). These findings are also in agreement with other studies on students' attitudes and perceptions in many other countries like China (Zhao et al, 2020), Malaysia (Ali, 2020), Indonesia (Mulyani et al, 2021;Angdhiri, 2020). For example, in Pakistan, Abbasi et al (2020) showed that 77% of Pakistani students negatively perceived eeducation.…”
Section: Advantages and Limitations Of Distance Education 2-what Are ...supporting
confidence: 82%
See 1 more Smart Citation
“…Further, concerning the practical aspects of the EFL education environment, students found it "less appealing and engaging due to its limitations" (Ali, 2020;Angdhiri, 2020;Abbasi et al, 2020). These findings are also in agreement with other studies on students' attitudes and perceptions in many other countries like China (Zhao et al, 2020), Malaysia (Ali, 2020), Indonesia (Mulyani et al, 2021;Angdhiri, 2020). For example, in Pakistan, Abbasi et al (2020) showed that 77% of Pakistani students negatively perceived eeducation.…”
Section: Advantages and Limitations Of Distance Education 2-what Are ...supporting
confidence: 82%
“…Therefore, it was not common to integrate new educational approaches presented by electronic instruction and educational applications and programs. Zhao et al (2020) state that universities find current technology that empowers online education provides working solutions and approaches for teaching students while reducing the negative effect of schools' closure.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of learners are affected by online learning in different ways. Zhao, Blankinship, Duan, Huang, Sun, Bak (2020) reported a study comparing teaching written and spoken Chinese individually to adult learners who had no prior proficiency of Chinese in the traditional classroom background and in the online setting. This study investigated the challenges and limitations of teaching Chinese as a foreign language.…”
Section: Past Studiesmentioning
confidence: 99%
“…The outbreak of the COVID-19 in March 2020 caused universities around the world to close the campuses and libraries, limit face-to-face contacts and switch to remote teaching in a very short time (Crawford et al, 2020;Zhao et al, 2020). Poland was no exception.…”
Section: Introductionmentioning
confidence: 99%
“…This sudden need to rely only on web-based teaching can be looked at as an unexpected radical change in the way we approach learning and teaching. Although the new technologies allowing online learning already existed however, the majority of courses offered by universities were face-to-face courses and it was not that popular to incorporate new teaching/learning solutions offered by e-learning platforms (Zhao et al, 2020). Online learning evolved from distance learning (Moore et al, 2011) which was popularized in Europe by the Open University, established in the UK already in 1969 (Woodley, 1981;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%